2020
DOI: 10.1016/j.chaos.2020.110214
|View full text |Cite
|
Sign up to set email alerts
|

Time series prediction for the epidemic trends of COVID-19 using the improved LSTM deep learning method: Case studies in Russia, Peru and Iran

Abstract: Highlights A predicting model for the long-term epidemic trend of COVID-19 by using LSTM with rolling update mechanism is proposed. The 150-days ahead epidemic trend of COVID-19 in Russia, Peru and Iran are estimated by our proposed model. The results provide that the epidemic of Peru will end in early December. The number of daily cases in Russia and Iran is expected to fall below 2000 and 1000 by mid-November and early December. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(92 citation statements)
references
References 18 publications
(16 reference statements)
1
82
0
5
Order By: Relevance
“…Besides, the machine and deep learning techniques such as ANN and LSTM have exhibited improvements in COVID-19 time series forecasting studies (e.g. [ 2 , 10 , 12 ]). Also, some methods based on fuzzy logic have been proposed in the literature(e.g.…”
Section: Covid-19 Time Series Forecastingmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, the machine and deep learning techniques such as ANN and LSTM have exhibited improvements in COVID-19 time series forecasting studies (e.g. [ 2 , 10 , 12 ]). Also, some methods based on fuzzy logic have been proposed in the literature(e.g.…”
Section: Covid-19 Time Series Forecastingmentioning
confidence: 99%
“…Also, in [9] , a new ensemble approach based on ANNs and fuzzy aggregation was proposed and its performance was evaluated on COVID-19 time series of Mexico and its 12 states which showed significant improvement than single ANN. In recent studies [ 2 , [10] , [11] , [12] ], deep learning methods such as LSTM and bidirectional LSTM (BiLSTM) have been utilized for COVID-19 time series forecasting . The results indicated that LSTM and its variants have good performance in predicting the COVID-19 time series.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Need for prompt human validation and response [1,[9][10][11][12]15,17,26,[63][64][65][66][67] Can AI mitigate the spread of biological diseases and guide early treatment?…”
Section: Key Questions the Promise Of Ai The Peril Of Ai Referencesmentioning
confidence: 99%
“…Refined analysis of poorly refined, incomplete, or biased data Abdication of human responsibility for triage decision-making [13][14][15][16][17][18]20,25,26,37,[69][70][71][72] How might AI accelerate development of medical therapies and treatment protocols?…”
Section: Key Questions the Promise Of Ai The Peril Of Ai Referencesmentioning
confidence: 99%